Clostridium difficile infection after restorative proctocolectomy and ileal pouch anal anastomosis for ulcerative colitis. (May 2016) - Martinez Ugarte, M. L.; Lightner, A. L.; Colibaseanu, D.; Khanna, S.; Pardi, D. S.; Dozois, E. J.; Mathis, K. L.
Abstract: Aim: Clostridium difficile infection (CDI) of the ileal pouch following restorative proctocolectomy (RPC) is becoming increasingly recognized. We aimed to understand better (i) the associated risk factors, (ii) treatment practices and (iii) the pouch diversion and failure rate in patients who developed CDI of the pouch after RPC for ulcerative colitis (UC). Method: Patients who tested positive for C. difficile of the pouch between 2007 and 2010 were included in the analysis. Data collected included patient demographics, time from RPC to documented CDI, the treatment of CDI and rate of excision of the pouch. Results: Of 2785 patients recorded in the hospital CDI database, 15 had had an RPC with ileal pouch anal anastomosis. The median age was 44 years and the median interval from RPC to first documented episode of CDI was 3 years. Thirteen (81%) patients had had multiple episodes of pouchitis before and after CDI infection, and all were symptomatic at the time of testing for CDI. Within 30 days of the diagnosis of CDI, six (40%) patients were taking immunosuppressive medication, seven (47%) were taking a proton pump inhibitor and 12 (80%) had received antibiotics. Five patients required hospitalization for CDI and four had severe infections characterized by a serum creatinine more than 1.5 times baseline ( n = 3) and a white cell count above 15 000 ( n = 1). Six patients who underwent endoscopy had severe inflammation of the pouch including the presence of a pseudomembrane in one case. Ten patients were treated with metronidazole alone and five with vancomycin. Two patients had recurrent CDI of the pouch during a median follow‐up period of 2.9 years and one had CDI refractory to medical management. This patient required diversion of the pouch with an ileostomy for refractory CDI but no patient required excision of the pouch. Conclusion: All 15 patients developing CDI of the pouch were successfully treated with antibiotics and only one required surgery in the form of an ileostomy.